Efeito do uso de parede verde na temperatura interna de modelo construído com bloco cerâmico - Seixas, Carolina Dinali Santos (2019)
Green walls are architectural alternatives considered beneficial in both scales, of buildings and in urban scale. In this work the green wall effect was evaluated from the reproduction in small scale of a building located at the UTFPR Câmpus in Londrina, known as Block S. Block S, as well as the other buildings of the institution, have one of their main façades facing North, and therefore, this was also the orientation of the two blocks built: without green wall (BSPV) and with the green wall (BPV). The monitoring of the air temperature and the relative humidity of the air occurred through the use of sensors HOBO and Arduinos associated to temperature sensors. In order to measure the reliability of the collected data, the sensor Arduino was calibrated after a comparative procedure performed with the HOBO sensor, which had been calibrated in previous experiments, therefore being a reliable reference. From the determination coefficient R² = 0,9695, it was possible to confirm the reliability of the collected data using the Arduino sensor. Aiming to perform the experiment, seedlings of four different types of ornamental plants were cultivated in greenhouses for six months, so that when they were fixated to build the green wall, they were already developed and with enough size to promote shade on the wall. The module consisted of plastic support that houses plants rooted on substrate containing soil, sand and organic compost (1: 1: 1) and providing automated watering every 12 hours. The experiment occurred through comparison between the two models of the building, first without the green wall followed by placement of the green wall on one of the models. Provided that, it was possible to verify whether both models would show similar results without the green wall, which indeed occurred. Then, after installing the green wall on one of the models, the monitoring of the internal air temperature was done during the period of a month, between March and April of 2019, with a data collection occurred in a frequency of two minutes. It was possible to identify a significant influence in the internal temperature of the model with the green wall, with reduction up to 6 degrees in relation to the internal temperature of the model without a green wall, and reduction up to 13 degrees in relation to the external temperature. Moreover, it was also determined that the biggest reductions in temperature occurred in the afternoon. Therefore, the green wall can be considered an effective alternative for the reduction of internal temperature of closed environments, if installed correctly and strategically positioned.